Zinc deficiency in ruminants and its management: A brief review - Yanuartono, Yanuartono; Indarjulianto, Soedarmanto; Paryuni, Alsi Dara (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2024)
Minerals are organic substances found in nature and living things. In ruminants, minerals are one of the crucial components of the body. One of the mineral elements that is very important for the body is Zinc (Zn). The prominent role of Zn in ruminants is the synthesis and degradation of carbohydrates, fats, proteins, and nucleic acids. Ruminants can experience Zn deficiency by showing clinical symptoms such as dermatitis, anorexia and parakeratosis, stunted growth, and nail damage. In contrast, ruminants can also experience Zn poisoning with various clinical symptoms such as general weakness, diarrhea, hemolytic anemia, and decreased body weight. Current Zn deficiency can be overcome by adding commercial supplement products containing Zn. This paper aims to add brief insights into the benefits and treatment of Zn deficiency in ruminants.